Analysis of the association between polymorphisms in MMP2, MMP3, MMP9, MMP20, TIMP1, and TIMP2 genes with white spot lesions and early childhood caries. Issue 4 (15th September 2015) - Antunes, Lívia Azeredo; Antunes, Leonardo Santos; Küchler, Erika Calvano; Lopes, Ludiana Barbosa; Moura, Alex; Bigonha, Rhyan Silva; Abreu, Fernanda Volpe; Granjeiro, José Mauro; de Amorim, Lidia Maria da Fonte; Paixão, Izabel Christina N. P.
Abstract : Background: Matrix metalloproteinases and their inhibitors might be involved in enamel formation. Aim: This study aimed to evaluate the association between polymorphisms in MMP2, MMP3, MMP9, MMP20, TIMP1, and TIMP2 with white spot lesions (WSL) and early childhood caries (ECC). Design: A cross‐sectional study was performed on 786 children aged from 2 to 6 years in Brazil. After clinical evaluation, they were classified into groups with disease (the presence of WSL and/or ECC) and without disease (the absence of WSL or ECC). Genotyping of the selected polymorphisms was carried out with TaqMan real‐time PCR, using genomic DNA extracted from buccal cells. Allele and genotype frequencies were compared between groups. Chi‐square test, odds ratio (OR), and logistic regression were used ( P ≤ 0.05). Results: The dmft score was 1.3 (SD: 2.4), and 41.34% of the children have at least one caries lesion. In MMP9, the GG genotype was more frequent in the group without disease ( P = 0.006). In a recessive model, WSL was associated with the marker rs1711437 in MMP20 ( P = 0.019; OR = 1.20, 95% CI 1.02–1.42). The marker rs1784418 in MMP20 showed an association between the allele G distribution for the WSL group ( P = 0.020; OR = 0.73, 95% CI 0.55–0.96). Conclusion: MMP9 and MMP20 are involved in WSL and ECC development.